The effect of perceived stress on depression in stroke: the chain mediating role of self-acceptance and self-perceived burden - Li, Bing; Peng, Chundi; Sui, Chunyan; Chen, Weiye; Miao, Xin; Zhou, Ye; Qiao, Zhengxue (Frontiers in Psychology, 2026)
BackgroundThis study aims to investigate the mechanism through which perceived stress affects depression symptoms by assessing the current status of depression symptoms and psychological characteristics in stroke patients.MethodsA total of 222 stroke patients were enrolled through convenience sampling at a tertiary general hospital in Harbin City during 2023–2024. Measurement tools included the patient health questionnaire-9, Chinese version of perceived stress scale, self-perceived burden scale and self-acceptance questionnaire. SPSS software was used for descriptive statistical analysis, t-test, analysis of variance, correlation analysis, multiple stepwise regression analysis and mediation effect test.ResultsIn this study, 67.12% of stroke patients had depression symptoms. The results of correlation analysis showed that perceived stress was significantly positively correlated with self-perceived burden and depression symptoms (r = 0.212–0.241, p < 0.01), and significantly negatively correlated with self-acceptance (r = −0.320, p < 0.01). Self-perceived burden was positively correlated with depression symptoms (r = 0.348, p < 0.01), and negatively correlated with self-acceptance (r = −0.255, p < 0.01). Self-acceptance was negatively correlated with depression symptoms (r = −0.304, p < 0.01). Mediation effect analyses showed that self-acceptance mediated significantly (95% CI [0.025, 0.117]); self-perceived burden mediated significantly (95% CI [0.003, 0.098]); and self-acceptance and self-perceived burden mediated significantly the chain of mediation in the relationship between perceived stress and depression symptoms (95% CI [0.005, 0.035]).ConclusionPatients with stroke have a relatively high level of depression symptoms. Through a chain path of reducing perceived stress, enhancing self-acceptance, and alleviating perceived burden, the depression symptoms of stroke patients can be effectively alleviated.